Screening for Vietnamese plant extracts with potential benefit for anti osteoclastogenesis - Huong, Le Thanh; Trang, Duong Thu; Hai Dang, Nguyen (Vietnam Journal of Science and Technology, 2021)
Bone's homeostasis is only achieved when there is a balance between bone formation and bone resorption. A metabolic disorder of bone-resorbing osteoclasts can lead to osteoporosis. Long-term use of anti-osteoporosis drugs can lead to undesirable side effects so traditional herbal can be a potential source of alternative medicine. In the present study, forty one Vietnamese plants (seventy methanol extracts) were screened for osteoclastogenesis inhibitory activities on RAW264.7 mouse macrophage cells. For the first time, 29 extracts from 24 species showed potential as effective inhibitors of osteoclastogenesis.